Coronary blood flow in myocardial infarction with nonobstructive coronary arteries. (25th November 2020) - Magnani, I; Toniolo, S; Rinaldi, A; Paolisso, P; D'Angelo, E.C; Bergamaschi, L; Bartoli, L; Donati, F; Angeli, F; Foa', A; Pizzi, C; Galie', N
Abstract: Background: Myocardial infarction (MI) is mainly caused by atherosclerotic plaque thrombosis but several registries show that in 1–13% of cases MI occurs in the absence of obstructive coronary artery disease (MINOCA) utilizing the conventional cut-off of <50% stenosis. MINOCA is generally related to coronary arteries abnormalities (epicardial or microvascular dysfunction – MINOCA-co). However, non-coronary conditions may underlie MINOCA as a consequence of supply-demand mismatch (MINOCA-nco). The TIMI flow gradient (TFG) and the corrected TIMI frame count (CTFC) are established methods able to respectively provide a qualitative and semiquantitative estimation of epicardial blood flow at rest. No studies have yet evaluated these indices in patients with MINOCA. Purpose: To evaluate the clinical characteristics of patients with MINOCA and the angiographic indices in MINOCA-co versus MINOCA-nco. Methods: Among all consecutive patients undergoing coronary angiogram at our Centre for MI based on the 4th Definition of Myocardial Infarction, the ones showing <50% coronary artery stenosis were retrospectively analyzed; patients with previous coronary stenting were excluded from the study. According to the presence or absence of pre-specified criteria of supply-demand mismatch (SAP >180 mmHg, DAP >110 mmHg, HR >110 bpm, Hb <6 gr/dl, SatO2 <91% or P/F ratio <300), the study cohort was divided into MINOCA-nco and MINOCA-co, respectively. We defined as slow flow phenomenon a TFG < = 2 and/or a CTFC >40 for the left anterior descending artery, >27 for the right coronary artery and >24 for the left circumflex. Results: 453 patients were retrospectively evaluated and 112 (24.7%) met the inclusion criteria. Mean age was 68±13.2 years and 41 (36.6%) were males. MINOCA-co was the more prevalent entity accounting for 73 (65.2%) patients while 39 (34.8%) were MINOCA-nco. The two subgroups presented similar baseline characteristics with regards to gender and classic cardiovascular risk factors including hypertension, hypercholesterolemia, diabetes and smoking habit. Peripheral vasculopathy was more prevalent in MINOCA-nco patients (MINOCA-nco=15.4% vs. MINOCAco= 4.2%; p=0.04). Regarding the angiographic indices, there was no statistically significant difference in TFG between subgroups; conversely, the number of patients with a slow flow phenomenon as defined by CTFC was significantly higher in the MINOCA-nco group (MINOCAnco= 25.7% vs. MINOCA-co=9.8%; p=0.039). Conclusions: Our data suggest that among patients with MINOCA clinical characteristics were not useful in differentiating between the two disease entities (MINOCA-nco vs. MINOCA-co). However, MINOCA-nco patients had higher coronary flow impairment as evaluated by CTFC. The pathophysiological reason is still not clear; we hypothesized that, in this clinical setting, an increased heart rate, systemic arterial pressure or low oxygen supply might worsen unbalanced coronary perfusion. Funding Acknowledgement: Type of funding source: None